Guidelines for Effective Professional and Academic Writing - Alison E. Lutz; Brian E. Myers; Nick T. Place (EDIS)
AEC-382, a 4-page fact sheet by A.E. Lutz, B.E. Myers, and N.T. Place, provides tips to keep in mind while composing professional documents.  it addresses the level of formality to use, the use of third person, how to improve the quality and structure of one's writing, and how to identify and properly cite scholarly sources. Published by the UF Department of Agricultural Education and Communication, November 2006.